Peningkatan Hasil Belajar Siswa Dalam Pembelajaran PKN Dengan Model Kooperatif Tipe TPS Di Kelas IV Sekokah Dasar - Kukuh Vandriani (Universitas Negeri Padang, 2021)
This research is motivated by the less varied learning of Civics methods and learning model of Civics used, less digging knowledge of students who ask questions related to teaching materials that are taught, not yet forming study groups in pairs, have not created group discussion. The purpose of this study is to describe the planning, implementation and learning outcomes of students in learning Civics model with cooperative type TPS. The type of this research is Action Research The classroom approach used is qualitative and quantitative. Subjects in the study were teachers and students of grade IV. The results showed improvement in student learning outcomes, namely cycle I was 67% and in cycle II 90%.